An electrically assisted device for protein crystallization in a vapor‐diffusion setup. (15th May 2013) - Flores‐Hernández, Edith; Stojanoff, Vivian; Arreguín‐Espinosa, Roberto; Moreno, Abel; Sánchez‐Puig, Nuria
<x xml:space="preserve">Abstract</x> A new easy‐to‐use device has been designed and implemented for electric field‐induced protein crystallization in a vapor‐diffusion configuration. The device not only controls crystal nucleation by means of the electrical current, but also favors crystal growth owing to its vapor‐diffusion setup. Crystallization was conducted in the presence of an internal electric field and direct current. The proteins investigated were lysozyme, as model protein, and 2TEL–lysozyme (a synthetic protein consisting of two tandem alpha helix motifs connected to a lysozyme moiety). Lysozyme crystals that grew attached to the cathode were larger than those grown attached to the anode or in the absence of an electric current. On the other hand, crystals of 2TEL–lysozyme qualitatively showed a better X‐ray diffraction pattern when grown in the presence of an electric current.